BNCC, educação física escolar e as práticas corporais de aventura: análise sobre a inclusão de unidade temática no currículo nacional e as orientações teórico-metodológicas para a prática pedagógica - Riva, Sidnei (2023)
This thesis is inserted in the “Society, Knowledge and Education” line of research and was developed with the support of the studies and the participation in the “Representations, Spaces, Times and Languages in Educational Experiences” (RETLEE) research group. The object of this survey is the thematic unit of adventure body practices in the curricular component of Physical Education in the Brazilian Common Core Curriculum (BNCC), by exploring the main goal of comprehending how the curricular prescription in the Physical Education component in BNCC includes and orientates, theoretically and methodologically, the teaching of contents regarding the adventure body practices thematic unit. To achieve this goal, this research was based on the following question: how the “adventure body practices” thematic unit and its contents were included, and what are its theoretical-methodological orientations for the pedagogical practice of the curricular component of school Physical Education in the BNCC? The qualitative and methodological approach of the documental research was supported by the Analysis of the Discourse as a tool of interpretation and critical production in the process of collecting, systematizing and analyzing data, which takes BNCC as the main documentary source. In the first chapter, it is discussed a brief historical review regarding the conceptions of the school Physical Education teaching in Brazil, besides discussing the relation between the national curriculum and the school knowledge of Physical Education. The second chapter develops incursions in the theoretical debates about the social interaction of the adventure body practices, its connection with the controlled risk and its relations with nature, about the adventure body practices in school Physical Education and its theoretical-methodological connections with this educational-pedagogical area. In the third chapter, the BNCC as national curriculum policy, the curricular guidelines for the Physical Education curricular component, and its school knowledge are developed. The fourth chapter presents the adventure body practices asthematic unit of school Physical Education in the BNCC as well as its theoretical-methodological orientations for the teaching of this thematic unit based on the BNCC national curriculum. Through this research, it was possible to conclude that this thematic is a recent theme for school Physical Education and it has much to contribute with the teaching and integral learning of the students. Also, it is recognized that there is a lack of solid theoretical basis, as well as a lack of criticism that is shown in the BNCC document, which reinforces uncertainties and minimizes the possibility of students’ integral education.